2019
DOI: 10.1038/s41467-019-13609-0
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-associated RNA–protein complexes promote pairing of homologous chromosomes during meiosis in Schizosaccharomyces pombe

Abstract: Pairing of homologous chromosomes in meiosis is essential for sexual reproduction. We have previously demonstrated that the fission yeast sme2 RNA, a meiosis-specific long noncoding RNA (lncRNA), accumulates at the sme2 chromosomal loci and mediates their robust pairing in meiosis. However, the mechanisms underlying lncRNA-mediated homologous pairing have remained elusive. In this study, we identify conserved RNA-binding proteins that are required for robust pairing of homologous chromosomes. These proteins ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 49 publications
0
78
0
Order By: Relevance
“…It has been found that subunits of SC in C. elegans are sensitive to aliphatic alcohols, thus have a liquid-liquid phase separation property (Rog et al 2017). We have shown that lncRNA-protein complexes in S. pombe exhibit phase separation properties, since 1,6-hexanediol treatment reversibly disassembled these complexes and disrupted the pairing of associated loci while the Rec8 axis remained in this treatment (Ding et al 2019). We then examined that if LinE in S. pombe also has liquid droplet properties.…”
Section: The Line Is a Stable Structurementioning
confidence: 78%
See 1 more Smart Citation
“…It has been found that subunits of SC in C. elegans are sensitive to aliphatic alcohols, thus have a liquid-liquid phase separation property (Rog et al 2017). We have shown that lncRNA-protein complexes in S. pombe exhibit phase separation properties, since 1,6-hexanediol treatment reversibly disassembled these complexes and disrupted the pairing of associated loci while the Rec8 axis remained in this treatment (Ding et al 2019). We then examined that if LinE in S. pombe also has liquid droplet properties.…”
Section: The Line Is a Stable Structurementioning
confidence: 78%
“…No SC central element-like transverse element has ever been found in S. pombe. The only structures observed in between homologous chromosomes are lncRNA/RNA-transcription termination protein complexes, which are liquid-liquid phase separation droplets that play an essential role in the recognition and pairing of homologous chromosomes (Ding et al 2019). Since the liquid crystalline-like, transverse elements of SC may play a direct role in crossover interference (Rog et al 2017), and no crossover interference exists in S. pombe, LinEs on the chromosome axis may play roles in crossover control in a different way from that of SC (Loidl 2006;Yamada et al 2017).…”
Section: Stability Of Linesmentioning
confidence: 99%
“…In particular, fission yeast expresses sme2, a meiosis-specific lncRNA that accumulates at its gene locus and mediates robust pairing [79]. In a recent study, several sme2 RNA-associated proteins (Smp) were identified and were found to be similarly required for robust pairing [80]. Acute addition of 1,6-hexanediol dissolves Smp foci and unpairs the sme2 RNA-decorated loci (Box 2).…”
Section: Phase Separation During Meiotic Recombinationmentioning
confidence: 99%
“…In this context, the formation of inter-chromosomal interactions between loci sharing the same set of protein regulators would stabilize the association of partially-condensed homologue chromosomes. Fulfilling this prophecy, recent work demonstrated that homologue chromosome pairing in yeast relies on ribonucleoprotein (RNP) complexes involving locally-transcribed, meiosis-specific long non-coding RNAs (lncRNAs; Ding et al, 2019 ).…”
Section: Inter-chromosomal Genome Architecturementioning
confidence: 99%